The Behaviour Characteristics in Early Detection of Breast Cancer among Islamic Boarding School Students - Maulidia, Hanum Rahma; Prabamurti, Priyadi Nugraha; Indraswari, Ratih (Journal of Public Health for Tropical and Coastal Region, 2024)
Introduction: Breast Self-Examination (BSE) is an effort of self-early breast cancer detection, which is recommended to be carried out routinely from the age of 12 years. As this campaign is important to reach out, especially to young people, this study has been conducted to evaluate the relationship between the student characteristics and their perception of BSE and breast cancer disease (susceptibility, severity, benefits, barriers, and self-efficacy), school supports, and media exposure might affect their behavior on implement BSE practice. This study focuseds on students in Islamic Boarding School Mijen, Semarang.Methods : This research is a descriptive study with a cross-sectional approach. The study population was 166 students of boarding school aged 12-21 years old who have experienced menstruation. The instrument used was a questionnaire and —data analysis was anlysed using Chi-square test.Results: The results showed that 50.6% of respondents students had good BSE practices with several related variables, are a family history of breast cancer (p = 0.048), knowledge (p = 0.0001), perceived susceptibility (p = 0.020), perceived severity (p = 0.001), perceived benefits (p = 0.005), perceived barriers (p = 0.007), and information on media exposure (p = 0.013).Conclusion: Most students at the Mijen Islamic boarding school have done BSE well. This is supported by having a history of breast cancer in the family and having good knowledge, perceived (susceptibility, severity, benefits, and barriers), and exposure to information media